A Case of Suspected Radiation-Induced Meningioma That Developed 36 Years after Radiotherapy for a Suprasellar Tumor - Onoda, Keisuke; Takaya, Yoshinori; Sashida, Ryohei; Fujiwara, Ren; Wakamiya, Tomihiro; Michiwaki, Yuhei; Tanaka, Tatsuya; Shimoji, Kazuaki; Suehiro, Eiichi; Yamane, Fumitaka; Kawashima, Masatou; Matsuno, Akira (Asian Journal of Neurosurgery, 2022)
Recently, the improvements in the prognosis of childhood brain tumors have made it necessary to consider the risk of radiation-induced brain tumor development in long-term survivors. In this report, we describe a case of radiation-induced meningioma (RIM) treated surgically 36 years after radiotherapy. A 46-year-old woman, who underwent craniotomy for suprasellar germ cell tumor at 10 years of age with additional postoperative radiotherapy, was admitted to the emergency room with consciousness disturbance and right hemiplegia. One year earlier, magnetic resonance imaging (MRI) revealed a 1-cm diameter tumor in the left middle cranial fossa. This MRI showed an enlarged brain tumor in same lesion with clearly enhanced by gadolinium. A RIM located on a left sphenoid ridge with a fast growth rate was diagnosed, and the gross total removal was achieved by a left frontotemporal craniotomy. Histological diagnosis of atypical meningioma (World Health Organization grade II) was made. RIMs are frequently atypical, anaplastic meningiomas that have already been treated with radiotherapy, making additional postoperative radiotherapy difficult; the removal rate must be increased to achieve a good prognosis. In the case of long-term survivors after childhood radiotherapy, a strict follow-up with the occurrence of RIM in mind is necessary.
Keywords: radiation-induced meningioma; atypical meningioma; craniotomy